Can Local African Communities be Empowered through Participatory Budgeting? - Madaha, Rasel Mpuya (International Journal of Social and Administrative Sciences, 2020)
Tanzania used to be one of the poorest countries in Africa. Although the country attained a middle-income status on 1st July 2020, the majority of grassroots communities have not experienced improvement in their standard of living. Participatory budgeting (PB) is one of the variants of public budgeting geared at community empowerment through participation of non-elected citizens in the management of public resources. This article has explored the intent of the participatory public budgeting in the empowerment of local communities in the Tanzanian context. The key questions are having marginalized people been empowered to participate in the PB? The study used a qualitative research design. The main unit of analysis was a district council. An administrative ward and a household served as secondary units of analysis. The findings have divulged that there is a framework for the implementation of PB capable of empowering communities in Tanzania. However, the PB structures have been underutilized. If the government commits to effective implementation of the existing set up of the PB process, allowing full participation of local communities at all levels, community empowerment can be attained. Overall, the article adds to a new body of literature on the contribution of PB on community empowerment. The article is useful to practitioners and academicians interested in the implementation of participatory approaches and community empowerment. The study is based on an original research.